Experimental study of falling films by simultaneous laser-induced fluorescence, particle image velocimetry and particle tracking velocimetry - Charogiannis,A; Markides,CN (2014)
measurement technique based on the simultaneous implementation of Laser-Induced Fluorescence (LIF),Particle Image Velocimetry (PIV) and Particle Tracking Velocimetry (PTV) has been applied to the study of wavyliquid falling film flows characterized by low Reynolds (Re) and Kapitza (Ka) numbers. The presently examined Renumber range was 2.2 – 8.2, while the Ka number range was 28.6 – 41.4. The experimental methodology wasdeveloped with the ultimate aim of allowing for the evaluation of the local and instantaneous film thickness, interfacialvelocity and velocity field from within the illuminated liquid volume underneath the wavy interface. The majorchallenges associated with the simultaneous implementation of the two optical diagnostic techniques were, firstly, thedevelopment of a refractive index correction approach allowing for liquids of different properties (surface tension andviscosity) to be tested, secondly, the identification of the location of the two liquid boundaries (solid-liquid and gasliquid)in the LIF images, and lastly, the isolation of out-of-plane reflections from primary scattering regions in the rawPIV images. Following a detailed account of the novel practices formulated and utilized in tackling the aforementionedchallenges, the efficacy of the proposed methodology is demonstrated through comparisons between laser-basedmeasurements conducted in flat films, film thickness measurements performed with a micrometer, and the solution tothe Navier-Stokes equation based on the assumptions of one-dimensional (1-D), steady and fully developed flow. Inaddition, sample film topology results are presented for a range of flow pulsation frequencies (1 – 8 Hz), while filmthickness and interfacial velocity time traces were reconstructed and are presented along with film thickness andinterfacial velocity statistical results for select flow conditions.